Isolation, Characterization, and Selection of Molds Associated to Fermented Black Table Olives - Bavaro, Simona L.; Susca, Antonia; Frisvad, Jens C.; Tufariello, Maria; Chytiri, Agathi; Perrone, Giancarlo; Mita, Giovanni; Logrieco, Antonio F.; Bleve, Gianluca (Frontiers in Microbiology, 2017)
Table olives are one of the most important fermented food in the Mediterranean countries. Apart from lactic acid bacteria and yeasts that mainly conduct the olive fermentation, moulds can develop on the brine surface, and can have either deleterious or useful effects on this process. From the food safety point of view, occurring moulds could also produce mycotoxins, so, it is important to monitor and control them. In this respect, identification of moulds associated to two Italian and two Greek fermented black table olives cultivars, was carried out. Sixty strains were isolated and molecularly identified as Penicillium crustosum (21), P. roqueforti (29), P. paneum (1), P. expansum (6), P. polonicum (2), P. commune (1). A group of 20 selected isolates was subjected to technological (beta-glucosidase, cellulolytic, ligninolytic, pectolytic and xylanolytic activities; proteolytic enzymes) and safety (biogenic amines and secondary metabolites, including mycotoxins) characterization. Combining both technological (presence of desired and absence of undesired enzymatic activities) and safety aspects (no or low production of biogenic amines and regulated mycotoxins), it was possible to select six strains with biotechnological interest. These are putative candidates for future studies as autochthonous co-starters with yeasts and lactic acid bacteria for black table olive production.